2022
DOI: 10.48550/arxiv.2202.00766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commensuration Effects on Skyrmion Hall Angle and Drag for Manipulation of Skyrmions on Two-Dimensional Periodic Substrates

C. Reichhardt,
C. J. O. Reichhardt

Abstract: We examine the dynamics of an individually driven skyrmion moving through a background lattice of skyrmions coupled to a 2D periodic substrate as we vary the ratio of the number of skyrmions to the number of pinning sites across commensurate and incommensurate conditions. As the skyrmion density increases, the skyrmion Hall angle is nonmonotonic, dropping to low or zero values in commensurate states and rising to an enhanced value in incommensurate states. Under commensuration, the driven skyrmion is channeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…Extensive studies of commensurability effects have shown that they are associated with distinctive behavior in many systems, including superconducting vortices [67][68][69] , colloidal particles 70 , Wigner crystals 71 , and vortices in Bose-Einstein condensates 72,73 . Much less work has been done on commensurability effects in skyrmion systems 74,75 . Recently, Reichhardt et al 75 investigated commensuration effects for skyrmions in periodic pinning and found that the skyrmion Hall angle is non-monotonic, dropping to zero at commensurate states and returning to a finite value for incommensurate states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies of commensurability effects have shown that they are associated with distinctive behavior in many systems, including superconducting vortices [67][68][69] , colloidal particles 70 , Wigner crystals 71 , and vortices in Bose-Einstein condensates 72,73 . Much less work has been done on commensurability effects in skyrmion systems 74,75 . Recently, Reichhardt et al 75 investigated commensuration effects for skyrmions in periodic pinning and found that the skyrmion Hall angle is non-monotonic, dropping to zero at commensurate states and returning to a finite value for incommensurate states.…”
Section: Introductionmentioning
confidence: 99%
“…Much less work has been done on commensurability effects in skyrmion systems 74,75 . Recently, Reichhardt et al 75 investigated commensuration effects for skyrmions in periodic pinning and found that the skyrmion Hall angle is non-monotonic, dropping to zero at commensurate states and returning to a finite value for incommensurate states.…”
Section: Introductionmentioning
confidence: 99%